Analisis Framing Pemberitaan Pemusnahan Arsip pada Media Online Kanal Kalimantan dan Koran Banjar - Gani Nur Pramudyo; Muhammad Rosyihan Hendrawan (UIN Maulana Malik Ibrahim Malang, 2022)
News is construction results on reality. Opinions can't be omitted when covering the news. Journalist saw perspective and subjective reason (value and ethics). Journalists' side can not be separated by the process of reporting events. Audiences have different interpretations from journalists. This article has a goal to investigate facts, problems, and media perspective on text media about Destruction of Records. The research was used qualitative approach with framing. Framing is a strategy or method of journalists who construct and process news discourse to serve the audience. The subject is news about “Destruction of Records” that taken from kanalkalimantan.com with entitled “26.585 Arsip Tahun 1973-1987 Biro Kepegawaian Setwilda Kalsel Dimusnahkan”, and banjarbaru.com with entitled “26.585 Berkas Arsip Dimusnahkan Karena Ini dan”. They were published on Wednesday, 22 April 2020. The analysis follows the framing analysis model by Pan Kosicki (1993). They started by identifying how journalists arrange the fact (syntactical structures), how journalists served news (script structures), how journalists write the fact (thematic structure), and how journalists emphasize the facts (rhetorical structures). Analysis unit refer to word or phrase in sentence, lexicon, graphics, metaphors and presuppositions in the news text. The finding show media lead audience to understand the achievement of Dispersip Kalsel that perform destruction record. Legal claims, assessment labels, evidence and photo are the key point to direct the audience